The CoExplorer Technology Probe: A Generative AI-Powered Adaptive Interface to Support Intentionality in Planning and Running Video Meetings - Park, Gun Woo (Warren); Panda, Payod; Tankelevitch, Lev; Rintel, Sean (DIS 2024, 2024)
Effective meetings are effortful, but traditional videoconferencing systems offer little support for reducing this effort across the meeting lifecycle. Generative AI (GenAI) has the potential to radically redefine meetings by augmenting intentional meeting behaviors. CoExplorer, our novel adaptive meeting prototype, preemptively generates likely phases that meetings would undergo, tools that allow capturing attendees' thoughts before the meeting, and for each phase, window layouts, and appropriate applications and files. Using CoExplorer as a technology probe in a guided walkthrough, we studied its potential in a sample of participants from a global technology company. Our findings suggest that GenAI has the potential to help meetings stay on track and reduce workload, although concerns were raised about users' agency, trust, and possible disruption to traditional meeting norms. We discuss these concerns and their design implications for the development of GenAI meeting technology. KEYWORDS: video meetings, effectiveness, effort, design, adaptive user interface, windowing system, speech recognition; intent recognition, technology probe RELATED RESEARCH Formative studies Mental Models of Meeting Goals: Supporting Intentionality in Meeting Technology Prototype studies Before meetings: What Does Success Look Like? Catalyzing Meeting Intentionality with AI-Assisted Prospective Reflection Before and during meetings: The CoExplorer Technology Probe: A Generative AI-Powered Adaptive Interface to Support Intentionality in Planning and Running Video Meetings During meetings: Are We On Track? AI-Assisted Active and Passive Goal Reflection During Meetings - Microsoft Research Between meetings: Designing Interfaces that Support Temporal Work Across Meetings with Generative AI